Computational Algorithms for Fast-Building 3d Carbon Nanotube Models with Defects - Rozas-Soto, R; Contreras-Fuentes, M; Alvarez-Guenchuman, J (2012)
Algorithms for generating defective carbon nanotubes have been developed and implemented in software. The algorithms were designed to create arrays of carbon atoms that form layers and interconnect. The parameters for construction were the following: Hamada indices that respond to topology (armchair, zigzag or chiral nanotubes) and diameter, the saturated or unsaturated nature of the nanotube, the length and, most importantly, the presence of defects that can be built individually or repetitively by rotating bonds, removing atoms, or adding additional carbon atoms. The output was written in a standard, exportable file format that contained atomic coordinates useful for further computational chemistry work. © 2012 Elsevier Inc.